Analisis Kesalahan Siswa Kelas VIII SMP Dalam Menyelesaikan Soal Pemecahan Masalah Berdasarkan Tahapan Kastolan - Wahyuni, Sri; Syarifuddin, Hendra; Arnawa, I Made (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
Mathematics is a learning science that can improve students' ability to solve a problem in Junior High School (SMP). However, many students still make mistakes when working on the questions. This article aims to describe a problem experienced by students when working on questions based on the Kastolan stages. This research is a qualitative descriptive research that uses data collection techniques, namely written tests and field notes. The subject of the research is to find students of class VIII SMP. the results of his research illustrate that there are three types of problems experienced by students when working on questions based on the Kastolan stages, namely, (1) conceptual errors, there are 46% of students who make this error; (2) procedural errors, 28% of students made this error; and (3) technical errors, there are 26% of students who make mistakes